Research on Primary Frequency Regulation Control Strategy of SCESS-DFIG-P2H Generating Station - ZHANG Yuying; LI Ji; XU Lei; CHANG Xiqiang; ZHENG Wenyuan; YU Jixuan; SUN Dongyang (Journal of Harbin University of Science and Technology, 2024)
In order to solve the problem that the frequency regulation characteristics of wind turbines are weak and a single energy storage device can’t meet the power and energy demand of the full time scale，the primary frequency regulation control strategy of SCESS-DFIG-P2H generating station is proposed. Firstly，according to the primary frequency regulation power output characteristics of the traditional synchronous unit，the power support required for the primary frequency regulation of the SCESS-DFIG-P2H generating station was determined. Secondly ，by analyzing the feasibility of electric hydrogen production unit ( P2H) as a large capacity controllable load to participate in system frequency regulation，and comparing the application characteristics of different energy storage media，the multi-energy collaborative frequency regulation method of SCESS and P2H load reduction is selected. Furthermore，a multi- energy cooperative primary frequency regulation control strategy is proposed according to the characteristics of SCESS-DFIG-P2H generating station with distributed super capacitor energy storage and centralized hydrogen production architecture. Finally ，the effectiveness and rationality of the proposed control strategy are verified by establishing the simulation model of the wind-storage- hydrogen station with different initial wind speed states.